Prosper or inexistence: Path to Attaining Happiness in the Millennial Era from the Perspective of Eastern Philosophers and Students. - Suwankiri, Donrudee (Thai Journal of East Asian Studies, 2012)
Background: The world we live in never ceased to be problematic even after the arrival of the new millennium. Technology has possessed and consumed people into state of emptiness, solitary and isolation. They began to suffer, become utterly mystified; they have nothing to hold on to. The only escape is to seek a way out of these conditions. Eastern philosophers are mankind’s intellectual guidance of wisdom and the students of the millennium era are those who determine the course of the future. Both agents form a method adaptable to the mentality and livelihood of society, taking them to a place where peace is sustainable and eternal. Objective: To research, compile, analyze, and synthesize the attitude on ways to attain happiness by eastern philosophers and students as a body of knowledge thereupon used as society’s way of living and means to reach eternal and sustainable happiness. Result: Identify ways to attain happiness conforming with the perspective and concept of eastern philosophers and students adaptable to the livelihood of the laypeople and society as a whole. Discussion and Conclusion: For eastern philosophers and students, the core to attaining happiness lies in enriching of our spiritual level out of selfishness and adhering to religious principles, moral/ethical conducts, detachment from all defilement and desire,the use wisdom to end suffering and attain peace of mind. Furthermore, it is about realizing the importance of harmonizing with nature and our surroundings.